LACK OF ACCESS RIGHTS TO HIGHER EDUCATION FOR INDONESIA MIGRANT WORKERS: LESSON LEARNT FROM UNIVERSITAS TERBUKA - Nadia Nurani Isfarin; Megafury Apriandhini; Madiha Dzakiyyah Chairunnisa (Journal of Research and Innovation In Open and Distance Learning, 2023)
As part of social rights, the fulfillment and the protection of the right to higher education is guaranteed through positive state action. The State is responsible for developing and maintaining an education system and educational institutions for everyone without discrimination. The State ensures the fulfillment of the right of education, including higher education, which must respond to students' needs different social and cultural conditions. Migrant workers are one of the groups with special needs for higher education. The lack of availability and accessibility (distance and time) of higher education in the destination country leads to the neglect of the migrant workers' more elevated education rights. Migrant workers have equal rights with other Indonesian citizens to get the right to non-discrimination education. This study addresses the protection of the right to higher education for Indonesian migrant workers in Hong Kong. Through a normative juridical approach, this research discusses the right to higher education, the guarantee of the right to higher education for migrant workers in international treaties, and the effort of Universitas Terbuka to fulfill requests to higher education for Indonesian Migrant Worker the higher education through distance learning for Indonesia migrant workers who are Universitas Terbuka's students in Hong Kong.